Erratum to "A numerical study on the role of geometry confinement and fluid flow in colloidal self-assembly" [Powder Technology 214/3 (2011) 283-291] - Fang, H.; Tade, Moses; Li, Q. (Elsevier, 2012)
The publisher regrets that the above article, which was intended for this special issue, was inadvertently published in a regular issue. The details of the original article is mentioned above.